REDEFINING THE DESIGN OF TARPON MONOPODS FOR MARGINAL FIELDS - Lee, Hsiu Eik (Universiti Teknologi PETRONAS, 2013)
In the race to produce from a marginal field with a greater return on investment, technological innovations such as the minimal platform concept were introduced like that of the Tarpon monopod. PETRONAS currently owns six Tarpons, all which are installed in Malaysian waters. There is, hence, a need to assess the characteristics of the Tarpons’ structural system. A single platform is chosen to represent the fleet of Tarpon Monopods owned by PETRONAS. This study envelops a simulation approach that will effectively evaluate four sets of different environmental criteria; PETRONAS Technical Standards (PTS) 34.19.10.30, Offshore Engineering Center UTP (OECU) Joint Density (T = 8 sec , T = 6 sec) and metocean criteria for the As Designed Worst Condition. The platform is modelled in SACS 5.3 suit of programs for its intact and damaged conditions by varying its guying system and soil foundation characteristics. For each scenario, a static in-place analysis with pile soil interaction is conducted to plot the caisson’s deflection and unity checks alongside their respective interpretation and take aways. The static analysis is complemented by Dynamic Amplification Factors obtained from the analysis of SACS Dynpac and Wave Response. A comparison is made against the platform’s ultimate strength obtained via the SACS Collapse module. The results show that the Tarpon is relatively insensitive to the soil beneath it in its intact condition. As expected, the as designed metocean induces the largest deflection of the caisson. The Tarpon’s integrity is highly sensitive to its guying condition – even failure of one of the three sets of guy cables may induce failure in unfortunate environmental conditions. The Tarpon monopod (in water depth 70m-80m) is not a very robust structure with its initiating mode of failure coming from its anchor piles.